A handbook of Wisdom : psychological perspectives - Sternberg, Robert Jeffrey 1949-; Jordan, Jennifer, 1982- (Cambridge, United Kingdom Cambridge University Press, 2005)
At a time when poor choices are being made by notably intelligent and powerful individuals, this book analyzes a form of reasoning and decision-making that is not only productive and prudent, but serves as well a beneficial purpose for society. A Handbook of Wisdom includes contributions from some of the most prominent scholars in the field of wisdom research. Written from multiple perspectives, including psychology, philosophy, and religion, this book gives the reader an in-depth understanding of wisdom's past, present, and possible future direction within literature, science, and society.
Keywords: Wisdom; Conducta; Inteligencia